(p+q)(z-px-qy)=1
"F=pz-p^2x-pqy+qz-pqx-q^2y-1=0"
"\\frac{dx}{F_p}=\\frac{dy}{F_q}=\\frac{dz}{pF_p+qF_q}=-\\frac{dp}{F_x+pF_z}=-\\frac{dq}{F_y+qF_z}"
"\\frac{dx}{z-2px-qy-qx}=\\frac{dy}{-py+z-px-2qy}=\\frac{dz}{p(z-2px-qy-qx)+q(-py+z-px-2qy)}="
"=-\\frac{dp}{-p^2-pq+p(p+q)}=-\\frac{dq}{-pq-q^2+q(p+q)}"
"\\frac{dp}{-p^2-pq+p(p+q)}=\\frac{dp}{0}\\implies p=a=const"
"\\frac{dq}{-pq-q^2+q(p+q)}=\\frac{dq}{0}\\implies q=b=const"
Substitute values into the initial equatio.
Then:
"(a+b)(z-ax-by)=1"
"z-ax-by=c_1"
"\\frac{dx}{z-2px-qy-qx}=\\frac{dy}{-py+z-px-2qy}=\\frac{dp}{0}"
"dy-dx=dp=a"
"y-x=c_2"
The general solution:
"F(c_1,c_2)=F(z-ax-by, y-x)=0"
Comments
Leave a comment